2017
DOI: 10.1007/s00595-017-1524-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of rectal gastrointestinal stromal tumors: an analysis of registry data

Abstract: Rectal GISTs showed high rates of local recurrence regardless of the surgical procedure. Perioperative treatment with imatinib may improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…Rectal GISTs are also rare in eastern countries, accounting for approximately 0.1% of all rectal neoplasms in South Korea (10). Yasui et al reported that of 737 GIST patients evaluated between 2003 and 2007 in Japan, 24 (3.3%) were rectal GISTs (21). All were in the lower rectum, within a median of 2.5 cm from the anal verge (21).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal GISTs are also rare in eastern countries, accounting for approximately 0.1% of all rectal neoplasms in South Korea (10). Yasui et al reported that of 737 GIST patients evaluated between 2003 and 2007 in Japan, 24 (3.3%) were rectal GISTs (21). All were in the lower rectum, within a median of 2.5 cm from the anal verge (21).…”
Section: Epidemiologymentioning
confidence: 99%
“…Complete curative resection of rectal GISTs is difficult because of its anatomical features (35), and choice of the surgical procedure may be difficult in patients with large tumors close to the anal verge. Rectal GISTs have a high rate of local recurrence regardless of the surgical procedure (21). Surgical treatment is yet to be standardized (20), but local resection, low anterior resection, abdominoperineal resection (APR), and pelvic exenteration are performed.…”
Section: Surgerymentioning
confidence: 99%
“…Approximately 75% of GISTs harbor oncogenic mutations in the receptor tyrosine kinases KIT and PDGFRA (platelet‐derived growth factor receptor alpha) . As compared to gastric GIST, rectal GIST are mostly caused by KIT mutations . Many of these KIT mutations are responsive to imatinib, a tyrosine kinase inhibitor (TKI).…”
Section: Introductionmentioning
confidence: 99%
“…Resection is generally the initial therapy for localized GIST without metastasis, but the rectum represents an especially difficult region for tumor removal . Yasui et al found that rectal GISTs frequently recur and most often in a locoregional distribution. Thus, perioperative imatinib has been shown to be effective in reducing locoregional and distant recurrences after tumor resection, even in patients with positive margins .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation